1997
DOI: 10.1161/01.cir.96.1.326
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenation of Hypoxic Human Umbilical Vein Endothelial Cells Activates the Classic Complement Pathway

Abstract: We conclude that (1) hypoxia and reoxygenation of HUVECs significantly increases iC3b deposition on HUVECs, (2) C3 deposition after hypoxia and reoxygenation is largely mediated by the classic complement pathway, and (3) HUVEC-surface expression of CD46 and CD55 increases after hypoxia and reoxygenation. These data demonstrate that hypoxia and reoxygenation of human endothelial cells activates the classic complement pathway despite an increase in complement C3 regulatory proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 36 publications
9
77
2
Order By: Relevance
“…Furthermore CD55 expression on endothelial cells was upregulated in the presence of both VEGF and tumour-conditioned media. Similar increases in expression of CD55 have also been reported with TNF-α, IL-1β, IL-4 and hypoxia (Collard et al, 1997;Hindmarsh and Marks 1998). Our data suggests that the tumour environment causes upregulation of CD55 on tumour-associated endothelium.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore CD55 expression on endothelial cells was upregulated in the presence of both VEGF and tumour-conditioned media. Similar increases in expression of CD55 have also been reported with TNF-α, IL-1β, IL-4 and hypoxia (Collard et al, 1997;Hindmarsh and Marks 1998). Our data suggests that the tumour environment causes upregulation of CD55 on tumour-associated endothelium.…”
Section: Discussionsupporting
confidence: 87%
“…Although the above evidence suggests a pivotal role of the classical pathway of complement for reperfusion injury, studies of the lectin pathways have suggested it is also involved (32,33). In vitro studies of endothelium found that both classical and lectin pathways may be activated under hypoxia/reperfusion condition.…”
Section: Activation Of the Lectin Pathway By Natural Igm In A Modelmentioning
confidence: 99%
“…There were no statistical differences between groups in any of the measures. 6). This is a normal finding in mice and is unlikely to be of pathogenic importance as glomeruli were histologically normal (see Fig.…”
Section: Effects Of Ig-and T-lymphocyte Deficiencies On Renal Functiomentioning
confidence: 99%